Unspeakable - Brown, Sandra, 1948- (New York, NY : Warner Books, 1998)
A deaf widow with a young son is unaware that she is at the center of a vengeful plan of an escaped convict.
Keywords: Fugitives from justice -- Fiction; Deaf women -- Fiction; Revenge -- Fiction; Texas -- Fiction